Crosslinking curing environment-friendly polyurethane waterproof coating and preparation method thereof
By using cross-linking curing technology and environmentally friendly raw material ratio in polyurethane waterproof coatings, the environmental protection problems and insufficient physical performance of traditional coatings are solved, solvent-free curing and coating film performance are achieved, and a more environmentally friendly and efficient waterproof construction solution is provided.
Patent Information
- Application Number
- CN202411440198.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional polyurethane waterproof coatings have environmental problems, including solvent volatiles, harmful substances pollution and construction environment pollution, and insufficient physical properties of the coating film.
Cross-linked curing environmentally friendly polyurethane waterproof coating is used to achieve solvent-free curing by reasonably comparing raw materials such as polyhydroxy compounds, pentaerythritol polyether, nano-silica aerogel, wollastonite powder and fly ash float beads, and solvent-free curing is achieved, improving the elasticity and durability of the coating film.
It realizes solvent-free curing, reduces construction environment pollution, improves the physical performance and waterproof effect of the coating film, meets environmental protection requirements, and provides safer and more effective waterproof construction solutions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproof coatings, and in particular to a cross-linked and cured environment-friendly polyurethane waterproof coating and a preparation method thereof. Background Art
[0002] At present, waterproof coatings account for about 30% of the waterproof construction. Polyurethane waterproof coatings have a large share in waterproof coatings due to their good waterproof performance and are widely used. Polyurethane waterproof coatings are reactive polymer waterproof coatings synthesized by polymerization reaction with isocyanate and polyether polyol as the main raw materials, a certain amount of solvent and an appropriate amount of plasticizer, curing agent and pigment filler. It is generally divided into two types: single component and two components. Single-component polyurethane waterproof coatings are polyurethane prepolymers. After coating, they react and cure with water or moisture in the air to form an elastic waterproof coating with rubber properties. During the film-forming process, a certain amount of carbon dioxide gas is easily generated, which produces some pores in the coating, thereby reducing the physical properties of the coating. The two-component polyurethane waterproof coating is composed of two components, A and B. Component A is a polyurethane prepolymer and component B is a curing component. During construction and application, components A and B are mixed evenly according to a certain ratio. After coating, they react and cure to form an elastic waterproof coating with rubber properties. Two-component polyurethane waterproof coatings are mainly petroleum asphalt polyurethane waterproof coatings, but their composition is complex and contains a large amount of volatile organic substances. Single-component polyurethane waterproof coatings contain certain organic solvents and free TDI and other harmful substances, which seriously pollute the environment and endanger human health.
[0003] With the enhancement of environmental awareness and the advancement of science and technology, new solvent-free and environmentally friendly polyurethane waterproof coatings have the advantages of no solvent volatilization, non-toxicity, odorlessness, pollution-free construction, and rapid curing compared with traditional tar-based and petroleum asphalt polyurethane waterproof coatings. During construction, the crosslinking agent first reacts with moisture in the air to generate unstable carbamic acid, which quickly decomposes to generate amines, which further react with isocyanate to generate urea bonds, which play a chain extension role, and finally react and cure to form a polyurethane waterproof membrane, which is significantly different from the moisture curing principle of other single-component or two-component polyurethane waterproof coatings, and it is more in line with the requirements of ecological development and environmental protection. Therefore, it is urgent to provide a cross-linked and cured solvent-free and environmentally friendly polyurethane waterproof coating. Summary of the invention
[0004] In view of the defects and shortcomings in the prior art, the present invention provides a cross-linked and cured environmentally friendly polyurethane waterproof coating and a preparation method thereof. The cross-linked and cured environmentally friendly polyurethane waterproof coating provided by the present invention solves the environmental problems existing in traditional polyurethane waterproof coatings, realizes solvent-free curing, meets environmental protection requirements, improves the comprehensive properties of the coating film such as elasticity and durability, and provides a safer and more effective solution for waterproof construction.
[0005] In a first aspect, the cross-linked, cured, and environment-friendly polyurethane waterproof coating provided by the present invention comprises the following raw materials in parts by weight.
[0006] 15-30 parts of polyhydroxy compounds; Pentaerythritol polyether 6-15 parts; 1-5 parts of anionic surfactant; 1-5 parts of nano-silica aerogel; Wollastonite powder 1-8 parts; 25-45 parts of fly ash floating beads; 10-25 parts of diisocyanate; Chlorinated paraffin 0.5~3 parts; 0.5 to 3 parts of N, N-dimethyl-2-hydroxyethylamine.
[0007] The cross-linked, cured, and environment-friendly polyurethane waterproof coating provided by the present invention effectively solves the environmental problems existing in the construction of traditional polyurethane waterproof coatings through a reasonable combination of raw materials. The reasonable ratio of polyhydroxy compounds, pentaerythritol polyethers, and diisocyanates in the coating makes it possible for the coating to have a suitable viscosity without adding any solvent, and no harmful gases are generated during the curing process, thereby ensuring a pollution-free construction environment. The addition of nano-silica aerogel and wollastonite powder improves the physical properties and waterproof effect of the coating, while the use of fly ash floating beads reduces the density of the coating and enhances the convenience of construction. In view of the problem of volatile organic compounds in traditional coatings, the formula of the present invention realizes solvent-free curing, meets environmental protection requirements, improves the elasticity and durability of the coating, and provides a safer and more effective solution for waterproof construction.
[0008] Preferably, the specific surface area of the nano-silica aerogel is 500-600 m2 / g, and the silica content is ≥99.8%.
[0009] Preferably, the chlorine content of the chlorinated paraffin is 45% to 60%, preferably chlorocarbon-52.
[0010] More preferably, the mass ratio of the nano-silica aerogel to the chlorinated paraffin is 1-3:0.5-1.5.
[0011] In the present invention, the nano-silica aerogel is a nano-porous lightweight inorganic material with good hydrophobic and temperature-resistant properties, and a specific surface area of up to 600m 2 / g, its density can be as low as 40kg / m³, its silicon dioxide content is ≥99.8%, it has thickening, thixotropic and reinforcing effects, and improves the density, hydrophobicity, impermeability and tensile strength of the coating. Chlorocarbon-52 is a light lubricating oil fraction of 250~400℃ in crude oil, obtained through acid and alkali refining, water washing, drying, white clay adsorption, chlorination and other processes. It is a colorless, translucent liquid, tasteless and odorless, with a relative density of 1.1~1.3g / cm 3 The chlorocarbon-52 used in the present invention can play the role of defoaming and plasticizing. In particular, the synergistic effect of nano-silica aerogel reinforcement and chlorocarbon-52 plasticizing in the system of the present invention can significantly improve the toughness and elongation at break of the coating film.
[0012] Preferably, the polyhydroxy compound is trimethylolpropane. Preferably, the diisocyanate is toluene diisocyanate.
[0013] In the present invention, trimethylolpropane and toluene diisocyanate interact with each other in the formula to improve the performance of the coating. The three typical hydroxymethyl groups on the trimethylolpropane molecule can react with toluene diisocyanate to form carbamate and urea bonds, thereby improving the waterproofness and mechanical strength of the coating. The coating can also interact with other additives to quickly form a dense waterproof film during the curing process and further improve the waterproof performance of the coating.
[0014] More preferably, the mass ratio of the trimethylolpropane, pentaerythritol polyether, nano-silica aerogel and wollastonite powder is 18-26:8-14:1-3:3-5.
[0015] In the present invention, trimethylolpropane and pentaerythritol polyether form a high-density polymer network through cross-linking reaction, thereby improving the mechanical strength and durability of the coating film. Nano-silicon dioxide aerogel further provides good thickening, reinforcing and hydrophobic effects, thereby enhancing the compactness and waterproof performance of the coating film. Wollastonite powder, as a functional reinforcing material, further improves the strength of the coating film and optimizes the dispersibility of the coating.
[0016] Preferably, the pentaerythritol polyether has a hydroxyl value of 500-600 mgKOH / g and a viscosity of 2000-3000 mPa·s at 25°C. In the present invention, the pentaerythritol polyether has a hydroxyl value of 500-600 mgKOH / g and a viscosity (25°C) of 2000-3000 mPa·s, is a colorless to light yellow liquid, has good thermal stability, and can be directly polymerized with diisocyanate and triethanolamine dodecyl sulfate to generate an interpenetrating network structure flame retardant end polymer.
[0017] Preferably, the wollastonite powder is a needle-shaped powder with a fineness of 800-1250 mesh and a density of 2.78-2.91 g / cm 3, hardness is 4.5~5, thermal expansion coefficient is 6.5×10 -6 mm / (mm·℃). In the present invention, the wollastonite powder is a needle-shaped powder with a high aspect ratio (such as not less than 20:1, such as 22:1 in the embodiment) obtained by ultrafine grinding and surface modification of fibrous and needle-shaped wollastonite powder blocks, which can replace other short fiber mineral materials, has low oil absorption value and is easy to disperse. It is used as a functional reinforcing material. In the system of the present invention, it can enhance the tensile strength and tear strength of the coating film, improve the physical and chemical properties, durability and weather resistance of the product, and can also reduce the oil absorption and enhance the corrosion resistance.
[0018] Preferably, the fly ash floating beads are hollow spherical microbeads with a tap density of ≤0.045 g / cm 3 , Specific surface area ≥ 600cm 2 / g, the mass fraction of SiO2 and Al2O3 is ≥80%. In the present invention, the fly ash floating beads are hollow spherical microbeads extracted from fly ash discharged from coal-fired power plants, which are easy to disperse and have the characteristics of fine particles, light weight, high strength, etc. The fly ash floating beads with the above performance indicators can increase the thickness, construction properties and density of the coating film, and improve the impermeability of the coating film.
[0019] Preferably, the anionic surfactant is triethanolamine dodecyl sulfate. In the present invention, triethanolamine dodecyl sulfate is used as an anionic surfactant, which has good wetting and dispersing properties and can well disperse nano-silicon dioxide aerogel, wollastonite powder fiber and fly ash floating beads. The boiling point of the triethanolamine dodecyl sulfate is preferably 100±10°C, the melting point is 133~137°C, and the molecular weight is 415.59.
[0020] Preferably, the mass ratio of the N,N-dimethyl-2-hydroxyethylamine to toluene diisocyanate is 0.5-1.5:15-23.
[0021] In the present invention, N, N-dimethyl-2-hydroxyethylamine is an auxiliary catalyst and a clear liquid reactive catalyst. The hydroxyl group in the N, N-dimethyl-2-hydroxyethylamine catalyst can react well with toluene diisocyanate. Its melting point is -59.0°C and its density is 0.89 kg / m 3 , viscosity 3.8MPa·s, solubility: miscible with water, soluble in ether and aromatic hydrocarbons.
[0022] Further preferably, the cross-linked curing environment-friendly polyurethane waterproof coating adopts the following raw materials in parts by weight: 18-26 parts of trimethylolpropane; 8-14 parts of pentaerythritol polyether; 2-4 parts of triethanolamine lauryl sulfate; 1-3 parts of nano-silica aerogel; 3-5 parts of wollastonite powder; 30-40 parts of fly ash floating beads; Toluene diisocyanate 15-23 parts; Chlorocarbon-52 0.5~1.5 parts; 0.5-1.5 parts of N,N-dimethyl-2-hydroxyethylamine.
[0023] The present invention adopts the preferred raw materials and dosage ratio, and the cross-linked curing environmentally friendly polyurethane waterproof coating can achieve significant performance improvement, so that the performance of the coating film is significantly improved, the flexibility and elongation at break are further improved, and at the same time, it has better environmental protection characteristics. Through the interaction of adding trimethylolpropane, pentaerythritol polyether, nano-silica aerogel and wollastonite powder, especially under the optimized ratio, the tensile strength, tear strength and toughness of the coating are significantly enhanced, and the durability of the coating film under different environments is ensured. The synergistic effect of nano-silica aerogel and chlorocarbon-52 plasticizer improves the flexibility and elongation at break of the coating, so that it shows better adaptability when dealing with structural deformation. The optimized raw material ratio and preparation process do not need to add any solvent, greatly reduce the emission of VOCs (volatile organic compounds), meet environmental protection requirements, and ensure the non-toxic and odorless characteristics of the coating. The present invention can ensure that the coating has excellent performance in practical applications, and has higher environmental protection and service life.
[0024] In a second aspect, the present invention provides a method for preparing the cross-linked and cured environmentally friendly polyurethane waterproof coating, comprising: mixing trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate, adding attapulgite, wollastonite powder fiber and fly ash floating beads, then adding diisocyanate and chlorinated paraffin, and finally adding N, N-dimethyl-2-hydroxyethylamine. The order of adding materials of the present invention can not only make each raw material fully play its role, but also avoid the negative impact caused by the trace moisture brought into the raw materials, and improve the storage stability of the coating.
[0025] Further preferably, the preparation method of the cross-linked curing environmentally friendly polyurethane waterproof coating comprises: mixing trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate, heating to 40-55°C, adding attapulgite, wollastonite powder fiber and fly ash beads, heating to 120±10°C and evacuating, then cooling to 55-65°C, adding toluene diisocyanate and chlorocarbon-52, heating to 85±5°C, reacting, cooling to 45-55°C, adding N,N-dimethyl-2-hydroxyethylamine, and stirring to a certain viscosity; preferably, the vacuuming time is 2-3h, the vacuum degree is 0.05-0.10MPa; and / or, the reaction time is 2-4h; and / or, the stirring time is 20-40min, and the viscosity is 5000-12000 centipoise. The present invention effectively removes trace moisture in the raw materials by vacuum dehydrating the raw materials at 120°C, avoids the negative effects caused by moisture, and improves the storage stability of the coating. At the same time, the optimized preparation conditions play a key role in improving the performance and environmental protection characteristics of the cross-linked and cured environmentally friendly polyurethane waterproof coating, and the reasonable reaction temperature and feeding sequence also optimize the reaction efficiency and product performance, ensuring the environmental protection and excellent mechanical properties of the coating.
[0026] The cross-linked and cured environment-friendly polyurethane waterproof coating provided by the present invention adopts wollastonite powder fiber with low oil absorption value and easy dispersion as functional reinforcing material, thereby enhancing the tensile strength and tear strength of the coating film. The present invention utilizes the synergistic effect of nano-silica aerogel reinforcement and chlorocarbon-52 plasticization to improve the toughness and elongation at break of the coating film. It does not contain organic solvents, and the VOCs content is less than 30g / kg, which is much lower than the standard and similar products of 100g / kg. There is no free toluene diisocyanate in the cured polyurethane waterproof coating, which is harmless to the environment and human body and belongs to an environment-friendly waterproof coating. The method of the present invention not only improves the performance of the polyurethane waterproof coating, but also significantly reduces the impact on the environment, and has broad application prospects. Moreover, the process of the present invention is reasonable. Before the polymerization reaction, raw materials such as trimethylolpropane, pentaerythritol polyether, triethanolamine dodecyl sulfate, attapulgite, wollastonite powder fiber and fly ash floating beads are vacuum dehydrated together under high temperature conditions, thereby avoiding the negative impact caused by trace moisture brought into the raw materials and improving the storage stability of the coating. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the examples of the present invention, unless otherwise specified, the raw materials used in the following examples are all industrial products purchased on the market. Or they can be prepared by known methods. If no specific techniques or conditions are specified in the examples, they are all conventional methods or carried out according to the techniques or conditions described in the literature in this field, or according to the product instructions. If the manufacturers of the reagents and instruments used are not specified, they are all conventional products that can be purchased through regular channels.
[0029] Example 1
[0030] This embodiment provides a cross-linked and cured environment-friendly polyurethane waterproof coating, the raw materials of which are measured by weight: 18 parts of trimethylolpropane; 8 parts of pentaerythritol polyether; 2 parts of triethanolamine lauryl sulfate; 3 parts of nano-silica aerogel; Wollastonite powder 5 parts; 38 parts of fly ash floating beads; Toluene diisocyanate 23 parts; Chlorocarbon-52 1.5 parts; 1.5 parts of N,N-dimethyl-2-hydroxyethylamine.
[0031] The present embodiment also provides a method for preparing the above-mentioned cross-linked and cured environmentally friendly polyurethane waterproof coating: trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate are mixed, the temperature is raised to 40°C, attapulgite, wollastonite powder fibers and fly ash beads are added, the temperature is raised to 110°C and vacuumed, then the temperature is lowered to 55°C, toluene diisocyanate and chlorocarbon-52 are added, the temperature is raised to 80°C, the reaction is carried out, the temperature is lowered to 45°C, N,N-dimethyl-2-hydroxyethylamine is added, and the mixture is stirred to a certain viscosity; preferably, the vacuuming time is 2h, the vacuum degree is 0.05MPa; and / or, the reaction time is 2h; and / or, the stirring time is 20min, and the viscosity is 5000 centipoise.
[0032] Example 2
[0033] This embodiment provides a cross-linked and cured environment-friendly polyurethane waterproof coating, the raw materials of which are measured by weight: 23 parts of trimethylolpropane; Pentaerythritol polyether 12 parts; 3 parts of triethanolamine lauryl sulfate; 2 parts of nano-silica aerogel; 4 parts of wollastonite powder; 35 parts of fly ash floating beads; Toluene diisocyanate 19 parts; 1 part of chlorocarbon-52; 1 part of N,N-dimethyl-2-hydroxyethylamine.
[0034] The present embodiment also provides a method for preparing the above-mentioned cross-linked and cured environmentally friendly polyurethane waterproof coating: trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate are mixed, the temperature is raised to 47.5°C, attapulgite, wollastonite powder fiber and fly ash beads are added, the temperature is raised to 120°C and vacuumed, then the temperature is lowered to 60°C, toluene diisocyanate and chlorocarbon-52 are added, the temperature is raised to 85°C, the reaction is carried out, the temperature is lowered to 50°C, N,N-dimethyl-2-hydroxyethylamine is added, and the mixture is stirred to a certain viscosity; preferably, the vacuuming time is 2.5 hours, the vacuum degree is 0.075 MPa; the reaction time is 3 hours; the stirring time is 3 minutes, and the viscosity is 8500 centipoise.
[0035] Example 3
[0036] This embodiment provides a cross-linked and cured environment-friendly polyurethane waterproof coating, the raw materials of which are measured by weight: 26 parts of trimethylolpropane; 14 parts of pentaerythritol polyether; 4 parts of triethanolamine lauryl sulfate; 2 parts of nano-silica aerogel; 4 parts of wollastonite powder; 33 parts of fly ash floating beads; Toluene diisocyanate 16 parts; 1 part of chlorocarbon-52; 1 part of N,N-dimethyl-2-hydroxyethylamine.
[0037] The present embodiment also provides a method for preparing the above-mentioned cross-linked and cured environmentally friendly polyurethane waterproof coating: trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate are mixed, the temperature is raised to 55°C, attapulgite, wollastonite powder fibers and fly ash beads are added, the temperature is raised to 130°C and vacuumed, then the temperature is lowered to 65°C, toluene diisocyanate and chlorocarbon-52 are added, the temperature is raised to 90°C, the reaction is carried out, the temperature is lowered to 55°C, N,N-dimethyl-2-hydroxyethylamine is added, and the mixture is stirred to a certain viscosity; preferably, the vacuuming time is 3 hours, the vacuum degree is 0.10 MPa; and / or, the reaction time is 4 hours; and / or, the stirring time is 40 minutes, and the viscosity is 12000 centipoise.
[0038] Comparative Example 1
[0039] One-component polyurethane waterproof coating purchased from the market.
[0040] Comparative Example 2
[0041] A one-component solvent-free polyurethane waterproof coating purchased from the market.
[0042] The performance of the cross-linked and cured environmentally friendly polyurethane waterproof coating according to the embodiment of the present invention and the existing polyurethane waterproof coating are shown in Table 1. The standard value is the technical index requirement of Type I in "Polyurethane Waterproof Coating" GB / T19250.
[0043]
[0044] It can be seen from the table that the cross-linked and cured environment-friendly polyurethane waterproof coating of the present invention has greatly improved tensile strength, tear strength and elongation at break, thereby significantly improving the waterproof effect and reducing the coating cost.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A cross-linked and cured environmentally friendly polyurethane waterproof coating, characterized in that: The following raw materials are included by weight: 15-30 parts of polyhydroxy compounds; Pentaerythritol polyether 6-15 parts; 1-5 parts of anionic surfactant; 1-5 parts of nano-silica aerogel; Wollastonite powder 1-8 parts; 25-45 parts of fly ash floating beads; 10-25 parts of diisocyanate; Chlorinated paraffin 0.5~3 parts; 0.5 to 3 parts of N, N-dimethyl-2-hydroxyethylamine.
2. The cross-linked and cured environmentally friendly polyurethane waterproof coating according to claim 1, characterized in that: The specific surface area of the nano-silica aerogel is 500-600 m2 / g, and the silicon dioxide content is ≥99.8%; and / or the chlorine content of the chlorinated paraffin is 45%-60%, preferably chlorocarbon-52.
3. The cross-linked and cured environmentally friendly polyurethane waterproof coating according to claim 2, characterized in that: The mass ratio of the nano-silicon dioxide aerogel to the chlorinated paraffin is 1-3:0.5-1.
5.
4. The cross-linked, cured, and environment-friendly polyurethane waterproof coating according to any one of claims 1 to 3, characterized in that: The polyhydroxy compound is trimethylolpropane; and / or the diisocyanate is toluene diisocyanate.
5. The cross-linked and cured environmentally friendly polyurethane waterproof coating according to claim 4, characterized in that: The mass ratio of the trimethylolpropane, pentaerythritol polyether, nano silicon dioxide aerogel and wollastonite powder is 18-26:8-14:1-3:3-5.
6. The cross-linked, cured, and environment-friendly polyurethane waterproof coating according to any one of claims 1 to 5, characterized in that: The anionic surfactant is triethanolamine dodecyl sulfate.
7. The cross-linked, cured, and environment-friendly polyurethane waterproof coating according to any one of claims 1 to 6, characterized in that: The mass ratio of the N,N-dimethyl-2-hydroxyethylamine to toluene diisocyanate is 0.5-1.5:15-23.
8. The cross-linked, cured, and environment-friendly polyurethane waterproof coating according to any one of claims 1 to 7, characterized in that: The following raw materials were used in parts by weight: 18-26 parts of trimethylolpropane; 8-14 parts of pentaerythritol polyether; 2-4 parts of triethanolamine lauryl sulfate; 1-3 parts of nano-silica aerogel; 3-5 parts of wollastonite powder; 30-40 parts of fly ash floating beads; Toluene diisocyanate 15-23 parts; Chlorocarbons - 520.5~1.5 parts; 0.5-1.5 parts of N,N-dimethyl-2-hydroxyethylamine.
9. The method for preparing the cross-linked and cured environment-friendly polyurethane waterproof coating according to any one of claims 1 to 8, characterized in that: include: The trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate are mixed, and then attapulgite, wollastonite powder fiber and fly ash floating beads are added, and then diisocyanate and chlorinated paraffin are added, and finally N, N-dimethyl-2-hydroxyethylamine is added.
10. The method for preparing the cross-linked and cured environment-friendly polyurethane waterproof coating according to claim 9, characterized in that: include: Mix trimethylolpropane, pentaerythritol polyether and triethanolamine dodecyl sulfate, heat up to 40-55°C, add attapulgite, wollastonite powder fiber and fly ash beads, heat up to 120±10°C and evacuate, then cool down to 55-65°C, add toluene diisocyanate and chlorocarbon-52, heat up to 85±5°C, react, cool down to 45-55°C, add N,N-dimethyl-2-hydroxyethylamine, and stir until a certain viscosity is achieved.
Citation Information
Patent Citations
Anti-sagging solvent-free single-component polyurethane waterproof coating and preparation method thereof
CN112341925A
Cited By
Solvent-free thick-coating polyurethane waterproof material as well as preparation method and application thereof
CN121086651A
A solvent-free thick-coat polyurethane waterproof material, a preparation method and application thereof
CN121086651B